The CIA made me do it: understanding the political economy of corruption in Kazakhstan - Yeager, Matthew G. (Crime, law and social change, 2012)
This article focuses on a widely publicized criminal prosecution recently completed in the U.S. District Court in New York City. It features an oil broker by the name of James Giffen who is accused of paying bribes totaling as high as $84 million dollars to high-ranking members of the government in Kazakhstan. This includes the President, the Prime Minister, and a former oil minister. Mainstream criminology tends to see these perpetrators as individual evil-doers who exploit opportunity structures, rational-choice purveyors of greed, or even as persons who experienced problems of social attachment as young people. To the contrary, this paper suggests that the pattern is firmly grounded in the geo-politics of oil in central Asia, in which governments and their multi-national oil companies are jockeying for lucrative oil reserves. In the instant case, there was circumstantial evidence that both the CIA, State Department, and even the Clinton White House knew what Mr. Giffen was doing in Kazakhstan, and looked the other way - so as to favor American, multi-national oil companies seeking low-cost oil leases from the Kazakhstan government.